2019
DOI: 10.1016/j.heliyon.2019.e03048
|View full text |Cite
|
Sign up to set email alerts
|

Normative beliefs about cyberbullying: comparisons of Israeli and U.S. youth

Abstract: We examined how normative beliefs about cyberbullying influenced the choice of electronic aggression in hypothetical peer-to-peer scenarios. Data was collected from 1097 Israeli and 1196 U.S. students in grades 5th-10th, who completed self-report surveys examining normative beliefs about cyberbullying, aggressive cyberstrategies, face-to-face verbal and relational aggression, and access to electronic devices. Israeli students had higher levels of all aggression measures than U.S. students, but access to electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Teachers should understand that using aggressive behavior as a strategy for disciplining students decreases their ability to treat students with dignity, to empathize with students, and to motivate students to perform better ( Mohr, 2013 ). Although the acceptance and rejection of aggressive behavior is not always related to behavior, but this (un)acceptability can influence individuals to think of aggressive strategies ( Peled et al., 2019 ). In their study, Peled et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers should understand that using aggressive behavior as a strategy for disciplining students decreases their ability to treat students with dignity, to empathize with students, and to motivate students to perform better ( Mohr, 2013 ). Although the acceptance and rejection of aggressive behavior is not always related to behavior, but this (un)acceptability can influence individuals to think of aggressive strategies ( Peled et al., 2019 ). In their study, Peled et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although the acceptance and rejection of aggressive behavior is not always related to behavior, but this (un)acceptability can influence individuals to think of aggressive strategies ( Peled et al., 2019 ). In their study, Peled et al. (2019) found that the acceptance of aggressive behavior can predict individuals to choose cyber aggression as an appropriate way.…”
Section: Discussionmentioning
confidence: 99%